Maternal solitude before the new guidelines in SARS-COV-2 times: a Brazilian cutting - Gilvânia Patrícia do Nascimento Paixão; Luana Moura Campos; Jordana Brock Carneiro; Chalana Duarte de Sena Fraga
ABSTRACT Aim To reflect on the lonely experience of women during the pregnancy-puerperal cycle in times of pandemic by the SARS-CoV-2 virus. Method Theoretical-reflective study on the new Brazilian guidelines for care for women during pregnancy, childbirth and postpartum in times of Covid-19 and its influence on the exacerbation of maternal loneliness. The discussion about the transformations of women in this period refers to Maldonado's studies. Results Motherhood is a lonely process for women. The new technical norms that are in force bring important changes in the assistance to this cycle, mainly with regard to the importance of social distance, which intensifies the feeling of loneliness and helplessness. Final considerations This reflection can guide health professionals, especially the work of nurses in the scope of obstetrics, so that during the assistance to women in the pregnancy-puerperal cycle, they pay attention to the subtlety of feelings of loneliness that can interfere with maternal well-being fetal.